IMPLEMENTASI KEGIATAN FUN LEARNING DALAM COOKING CLASS KURIKULUM MERDEKA DI POCENTER - Madina, Bidarianti M; Kristiana, Dian (Media Inovasi Pendidikan dan Pembelajaran, 2025)
Early childhood education (PAUD) is very important in laying the foundation for children's growth and development in this era of globalization and technological progress. The